Beyond The Hijab: Subjective Experiences of Indonesian Muslimah Basketball Players - Kartiko, Dwi Cahyo; Rakhmawati, Deny Efita Nur (el Harakah: Jurnal Budaya Islam, 2020)
This study aimed to explore the negotiation of Islam identity reflected from the hijabi basketball players' subjective experiences in Indonesia. A qualitative method was conducted from a subjectivist epistemological position. Six hijabi basketball players between the ages of 16 and 30 were recruited to participate in this study. The data were collected through semi-structured interviews. A thematic analysis was adopted to analyze the data since this analysis method allows the researchers to interpret based on the data's in-depth examination. The study results showed that the negotiation of Islam identity was found in the ways of modifying their sports attires and behaviors in and out of the basketball fields. All of the participants saw their modifications as positive actions to integrate the Islamic values in their lives. Tujuan penelitian ini adalah untuk mengetahui negosiasi identitas Muslim yang direfleksikan dari pengalaman para pemain bolabasket yang berhijab di Indonesia. Penelitian kualitatif ini menggunakan subjectivitas epistemologis. Enam pemain dari usia 16 hingga 30 tahun dipilih menjadi partisipan. Data dikumpulkan melalui interview semi struktural. Sedangkan analisa datanya merupakan analisa tematik karena dalam interpretasi data diperlukan pemeriksaan yang detail dan mendalam. Hasil analisa data menunjukkan bahwa negosiasi Identitas sebagai orang Islam dilakukan dengan cara memodifikasi kostum olahraga dan sikap mereka baik di dalam maupun di luar lapangan bolabasket. Mereka memandang penyesuaian tersebut sebagai tindakan yang positif untuk menerapkan nilai–nilai Islam di dalam kehidupan mereka.